KONTRIBUSI MATA KULIAH AKHLAK TASAWUF TERHADAP KEDISIPLINAN DAN AKHLAKUL KARIMAH MAHASISWA SEKOLAH TINGGI AGAMA ISLAM (STAI) PANCA BUDI PERDAGANGAN - Muhammad Wahyudi; Mega Dini Fitriani; Khusnul Khotimah Nasution (Jurnal At-Tabayyun, 2022)
One of the problems being faced by our world of education today is how to improve noble character, especially among students. On the other hand, most students have low understanding and experience of Islam, caused by the low quality of Islamic education. The Tasawuf Morals course accepted by students has not had a positive function in cultivating noble morals due to several factors, including inadequate curriculum content, limited supporting facilities and infrastructure, weak mastery of material and teaching methodology, and inadequate number and quality of teaching staff. This study aims to explain and analyze: First, the contribution of discipline in attending lectures to the development of akhlakul karimah students of STAI Panca Budi Trading. Second, the contribution of the Tasawuf Akhlak course to the development of akhlakul karimah students of STAI Panca Budi Commerce. Third, the contribution of the Sufism Akhlak course plus the discipline of attending lectures to the moral development of STAI Panca Budi Commerce students. This research uses quantitative methods. Sources of research data consist of primary and secondary. Data collection tools are questionnaires, documentation and observation techniques. While data analysis used simple regression statistics and multiple linear regression. Based on the results of the research, it is empirically proven that the Tasawuf Morals course and the discipline of attending lectures simultaneously are able to partially make a real and positive contribution to the development of good morals for STAI Panca Budi Commerce students.